Pengenalan Kurikulum Merdeka Belajar Pada Siswa Pondok Pesantren Menggunakan Modul Ajar - Rica Wijayanti Wijayanti; Rifky Maulana Yusron; Didik Hermanto; Anindita Trinura Novitasari (Cv. Utility Project Solution, 2022)
The Merdeka Belajar curriculum is a manifestation of the real changes made by the government in the field of education as an effort to improve the quality and quality of education in Indonesia. This 2022-2023 school year, the government hopes that several schools will be able to implement learning with an independent learning curriculum. However, the fact that lapagan, especially among schools based on islamic boarding schools, the independent learning curriculum is not easy to implement without special assistance from experts. Therefore, we as part of the educators try to help the government to introduce the learning process with an independent learning curriculum in Islamic boarding schools. Our partner is Pondok Pesantren Al-Azizah 1 Bancaran, Bangkalan Regency. Our method of service is to introduce the learning process of the independent learning curriculum to students and students using the help of teaching modules that we have compiled before. Based on the results of this service program, we can draw the conclusion that the existence of modules that are designed by themselves according to the level of characteristics of students and students can make it easier to implement the learning process of the independent learning curriculum. In addition, the introduction of the independent learning curriculum that we do to the community in partner schools can help them construct their own knowledge using the learning experiences they already have. This indirectly gives rise to creative ideas